1994
DOI: 10.1152/ajpgi.1994.266.3.g444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of histamine on rat gastric H(+)-K(+)-ATPase alpha-subunit expression

Abstract: The H(+)-K(+)-adenosinetriphosphatase (ATPase) is expressed in the parietal cell and is responsible for acid secretion by the stomach. Histamine binds to an H2 receptor and activates adenylate cyclase and intracellular calcium concentration ([Ca2+]i) elevation, stimulating acid secretion. It has been shown that omeprazole administered to rats increases serum gastrin and transiently increases the level of mRNA for the alpha-subunit of the pump, but this increase is blocked by the presence of the H2-receptor ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The oxyntic mucosal H + K + ‐ATPase mRNA abundance increased with acid secretion and was significantly higher than basal after 1 h with carbachol, lagging slightly behind the increase in acid secretion. The time‐scale and the relative increase of H + K + ‐ATPase mRNA abundance is comparable to that observed after histamine infusion in rats anaesthetized with pentobarbitone (Tari et al , 1994). Similar increases in H + K + ‐ATPase mRNA abundance have also been described in purified preparations of canine parietal cells in response to histamine and carbachol (Campbell & Yamada, 1989).…”
Section: Discussionsupporting
confidence: 52%
“…The oxyntic mucosal H + K + ‐ATPase mRNA abundance increased with acid secretion and was significantly higher than basal after 1 h with carbachol, lagging slightly behind the increase in acid secretion. The time‐scale and the relative increase of H + K + ‐ATPase mRNA abundance is comparable to that observed after histamine infusion in rats anaesthetized with pentobarbitone (Tari et al , 1994). Similar increases in H + K + ‐ATPase mRNA abundance have also been described in purified preparations of canine parietal cells in response to histamine and carbachol (Campbell & Yamada, 1989).…”
Section: Discussionsupporting
confidence: 52%
“…[30][31][32] Based on earlier reports, one of the pathways that stimulates ATPase gene expression is as follows: gastrinAEgastrin/CCK-B receptor of ECL cellsAE histidine decarboxylase gene activationAEhistamineAE H 2 receptor of parietal cellsAEcAMP/intracellular calcium concentration ([Ca 2ϩ ]i) AEH ϩ , K ϩ -ATPase gene activation, and morphological activation (stimulation). [27][28][29] The present study demonstrated that the histamine content of the fundic mucosa was higher with omeprazole treatment than with rabeprazole treatment. In addition, the increase in H ϩ , K ϩ -ATPase mRNA was markedly greater with omeprazole treatment than with rabeprazole treatment, and the difference was significant at a dose of 100mg/kg.…”
Section: Discussionmentioning
confidence: 79%
“…27 Thus, the elevation of histamine, not gastrin, is the most significant factor promoting an increase in ATPase gene expression and the transformation of parietal cells to a more stimulated state. 27,28 Our previous experiments have also demonstrated that the morphological activation of parietal cells induced by hypergastrinemia, and the subsequent increase of H ϩ , K ϩ -ATPase synthesis by these cells, are mediated by an increase in histidine decarboxylase gene expression in ECL cells that is stimulated through the gastrin/cholecystokinin (CCK)-B receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histamine then, via paracrine diffusion, interacts with parietal (oxytinic) cells, stimulating the upregulation of surface H + /K + proton pumps and thus the secretion of acid [51, 60]. Gastrin itself and acetylcholine also act directly on parietal cells through surface receptors to stimulate acid secretion; in this case, histamine potentiates the activity of gastrin, but this effect is still secondary to the stimulation of acid secretion by histamine [6165]. Gastrin may also sensitize parietal cells to other acid secretagogues [66].…”
Section: Physiological Roles Of Gastrin In the Stomachmentioning
confidence: 99%